Nel Noddings as Social (Studies) Educator. Issue 4 (2nd October 2018) - Thornton, Stephen J.
Abstract : Nel Noddings has presented a distinctive view of education that is relational in outlook. Although all of her writing holds implications for social education broadly construed, a subset of it addresses the school subject of social studies directly. This article mainly concerns what Noddings has said and implied about chief constructs of the latter. In particular, I look at (a) critical thinking, (b) what should be taught, and (c) what the foregoing suggest for teacher education. I conclude that her work holds great potential to reconstruct social studies theory and practice.